Analysis of Flood Disaster Mitigation Through Spatial and Environmental Policies for Flood Management in Bekasi City, West Java - Suprapti Widiasih; Faizah Julina; Sri Susanti Widyasari (Journal of General Education and Humanities, 2026)
Flood risk in rapidly urbanizing areas such as Bekasi City continues to increase due to land-use change, weak spatial control, and limited policy integration. This study aims to analyze the effectiveness of spatial and environmental policy implementation in flood mitigation and to identify key supporting and inhibiting factors. This research employs a descriptive qualitative approach using in-depth interviews and Focus Group Discussions (FGDs) with government agencies, non-government organizations, and community representatives in flood-prone areas. Data were analyzed using NVivo through coding, thematic categorization, and pattern analysis based on the Mazmanian and Sabatier policy implementation model. The findings reveal that flood mitigation effectiveness is primarily constrained by weak regulatory enforcement, fragmented inter-agency coordination, and limited technical and financial capacity. These issues indicate that policy challenges are structural and governance-related rather than purely technical. The study highlights that ineffective integration between spatial planning and disaster risk management remains a critical barrier to reducing flood risk. This study concludes that improving flood mitigation requires strengthening collaborative governance, integrating risk-based spatial policies, and developing adaptive infrastructure supported by integrated disaster information systems. Compared to previous studies, this research offers a novel contribution by applying NVivo-based thematic analysis to systematically examine policy implementation dynamics, providing a more comprehensive and evidence-based understanding of urban flood governance.